The Comparative Poetics of Homeric Literary Imitation from Antiquity to Renaissance France : Aphrodite's Charm - Nassichuk, John, (Late Antiquity and Medieval Studies E-Books Online, Collection 2024., 2025)
Aphrodite's famous ribbon known as the cestus , the irresistible love charm that she loaned to Hera in the Iliad, was, thanks to a fruitful early misreading, transformed by ancient, medieval, and Renaissance authors into a symbol of honorable feminine chastity: in Maurice Scève's 1560 Microcosme , an epic rewriting of Genesis, Eve first appears before an astonished Adam wearing the virginal cestus as a symbolic guarantee of her sexual innocence. This book traces the history of this curious development from Homer to the end of the sixteenth century in France. Through analyses of both famous and little-known texts, it illustrates the complexity and fecund liberty of Homeric reception.